HIV and tuberculosis: A historical perspective on conflicts and challenges. (May 2020) - Canetti, Diana; Riccardi, Niccolò; Martini, Mariano; Villa, Simone; Di Biagio, Antonio; Codecasa, Luigi; Castagna, Antonella; Barberis, Ilaria; Gazzaniga, Valentina; Besozzi, Giorgio
Abstract: Tuberculosis is an ancient infectious disease caused by the bacillus Mycobacterium tuberculosis that is still nowadays afflicting humans all over the world. It causes ill-health for 10 million people each year. Tuberculosis (TB) has been the leading cause of death from a single infectious agent, ranking above HIV/AIDS. In recent years, infection with HIV represents a major risk factor predisposing for infection and TB is the most common cause of AIDS-related death. Despite the treatment of HIV-associated TB has essentially retraced that recommended in HIV-negative cases, it has disclosed some additional challenges over the years. The association of delayed and missed diagnoses, logistic accidents and some well-known complications of HIV and TB treatment co-administration has contributed to 300, 000 people living with HIV died from a preventable and curable disease like TB in 2017. The evaluation of new diagnostic and therapeutic approaches with the struggle to erase stigma are essential to successfully manage HIV-TB coinfection.